2019
DOI: 10.1002/jbm.a.36628
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term evaluation of thromboresistance of a poly(ether ether ketone) (PEEK) mechanical heart valve with poly(2‐methacryloyloxyethyl phosphorylcholine) (PMPC)‐grafted surface in a porcine aortic valve replacement model

Abstract: Improved thromboresistance of mechanical valves is desired to decrease the risk of thromboembolism and thrombosis and reduce the dosage of anticoagulation with a vitamin K antagonist (e.g., warfarin). For several mechanical valves, design‐related features are responsible for their improved thromboresistance. However, it remains unclear whether material‐related features provide a practical level of thromboresistance to mechanical valves. Here, we studied the effect of a bileaflet valve made of poly(ether ether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Furthermore, the modified surface will not only prevent bacterial adhesion and biofilm formation 24,25 but also improve thromboresistance. 24,26 Previously we developed a bearing surface modification technology of the acetabular liners used in artificial hip joints. [27][28][29] Our previous studies on the biomedical efficacy and safety of the acetabular liners with a PMPC graft layer (~100-nm-thick 23 ), as a bearing surface modification layer, revealed that hydrated gel-like layers greatly enhance the wear resistance of the CLPE bearings.…”
mentioning
confidence: 99%
“…Furthermore, the modified surface will not only prevent bacterial adhesion and biofilm formation 24,25 but also improve thromboresistance. 24,26 Previously we developed a bearing surface modification technology of the acetabular liners used in artificial hip joints. [27][28][29] Our previous studies on the biomedical efficacy and safety of the acetabular liners with a PMPC graft layer (~100-nm-thick 23 ), as a bearing surface modification layer, revealed that hydrated gel-like layers greatly enhance the wear resistance of the CLPE bearings.…”
mentioning
confidence: 99%
“…Polymeric heart valves have attracted much attention ( Bezuidenhout et al, 2015 ; Guo et al, 2019 ; Kambe et al, 2019 ). Xing Zhang and coauthors reported that a composition of PEGDA hydrogels and polyethylene terephthalate/polyamide6 (PET-PA6) fabric (PEGDA/PET-PA6) was fabricated to form artificial heart valve leaflets ( Guo et al, 2019 ).…”
Section: Anti-biofouling Polymers With Special Surface Wettability For Biomedical Applicationsmentioning
confidence: 99%
“…[ 38 ] In addition to heparin, zwitterionic polymers showed potential anticoagulant properties. [ 44,45 ] Zwitterionic polymers contained both positive and negative charges and remained net neutral. The zwitterionic polymers formed a hydration layer with water molecules due to the equal and opposite charges, [ 46 ] which repelled non‐specific protein adsorption, reduced contact activation of intrinsic pathway and further inhibited blood coagulation.…”
Section: Immunocompatibility Of Engineered Tissue or Organ‐based Implantsmentioning
confidence: 99%